A EMPOWERMENT OF MOTHERS IN CARE OF CHILDREN WITH STUNTING IN PERCUT SEI TUAN VILLAGE: STUNTING - Triwibowo, Cecep Triwibowo; Lestari; Juliana (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Stunting events that have occurred since childhood are associated with slower motor development and lower intelligence levels (Martorell et al. 2010). Several studies show that children who experience stunting during their toddler years have low cognitive levels, poor learning and psychosocial achievement (Achadi 2012). The incidence of stunting in toddlers is one of the global nutritional problems. Based on UNICEF data from 2000-2007, it shows that the prevalence of stunting in the world reached 28%, in South Asia it was 38% and in eastern and southern Africa it was 40%. When compared with the